Indigenous communication in Latin America for social re-existence: communicative experiences in the Colombian Cauca. - Linares Sánchez, Malely; Postigo-Gómez, Inmaculada (Taylor&Francis, 2022)
This paper is a contribution to the field of communication in Latin America through the theoretical proposal called communication for social re-existence. This concept arises as a result of the analysis of community practices in which communication and territorial defense are interrelated and led by the Nasa indigenous people in the Cauca region of Colombia. This communicative approach is represented through the metaphor of a fabric, built by knots (the participating actors), gaps (spaces for reflection) and threads (the strategies). This research hopes to be the beginning of a communicative methodology that will be useful within the organizational proposals of the subaltern movements.
Keywords: Pueblos indígenas - Colombia - Situación social; Comunicación - Colombia; Cauca; Latin America; Communication; Re-existence; Subalternity; Territory